Краєзнавчо-туристична оцінка Старостинського замку в Галичі - Лисий, І. (Краєзнавство, 2018)
На основі застосування авторського алгоритму, що поєднує чотири групи оціночних блоків (природно-географічна, історико-культурна, інфраструктурна та інформаційно-рекламна) проведено
комплексну краєзнавчо-туристичну характеристику аналіз просторово-географічної локалізації, архітектурного стану, історико-культурної цінності, атрактивного потенціалу Старостинського замку, який розташований в м. Галич Івано-Франківської обл. In this article was made historic, cultural and touristical descriptive analysis of little-known Starosta castle
in Halych, which is located in Ivano-Frankivsk region, on the base of using of four groups of characteristics:
natural and geographical (morphological features of the monument’s construction, hydrological characteristics
of the territory, location near from objects of the natural reserve fund, presence in the castle complex handmade
recreational forests, landscaped parks, gardens and landscaped gardens, aggregate indicators of the natural and
geographical location), historical and cultural (degree of the physical preservation, level of the historical
significance, degree of the cultural value, indicator of the architectural and stylistic value, availability of saved
elements of historic defense systems), infrastructural (transport accessibility, availability of accommodation
facilities, food establishments, museum institutions, specialized souvenir shops and stalls), informational (integration
to the tourist routes, organization of tourist promotional campaigns, exhibitions and fairs, availability
of informational and advertising data, rank of the coverage in scientific tourism profiles and degree of the
saturation of the Internet with tourist information). It was identified main positive and negative points of the
potential adaptation of monument for tourism and recreation. На основе применения авторского алгоритма, который объединяет четыре группы оценочных блоков
(естественно-географическая, историко-культурное, инфраструктурная и информационно-рекламная)
проведена комплексная краеведческо-туристическая характеристика пространственно-географической
локализации, архитектурного состояния, историко-культурной ценности и атрактивного потенциала
Старостинского замкового комплекса, который расположен в г. Галич Ивано-Франковской обл.